Demand Supply Interaction and Price Formation: An Analysis of Contemporary Market Equilibrium - Pratiwi Musa, Kartika Septiary (International Humanity Advance, Business & Sciences, 2025)
This study aims to understand how the relationship between demand, supply, and market equilibrium is formed in a traditional market environment. The study used a descriptive qualitative method, conducting direct observations and interviews with traders and buyers at Makassar City's Central Market. The primary focus of this study was to analyze how market participants adapt to changing prices and economic conditions through social interactions and everyday experiences. The results indicate that price equilibrium in traditional markets is formed naturally through adjustments between the quantity of demand and supply of goods. When demand increases, prices rise; conversely, when supply increases, prices decrease. Other factors such as seasonality, purchasing power, and trust among market participants also influence price equilibrium. The conclusion of this study is that market mechanisms are influenced not only by economic figures but also by social behavior, intuition, and human experience in trading activities.